CHILD [AND] ACCOUNTING - Krisno Septyan (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
children and love, they have been on the fringes of the accounting discussion, they are not logocentric accounting,a pitty. Keywords: child; accounting; solipsism